Pengaruh pemberian pupuk bokashi terhadap produksi bahan segar bahan kering serta bahan organik rumput setaria - Joni Yiwa Lakar; Herayanti Panca Nastiti; Ni Nengah Suryani (Jurnal Peternakan Lahan Kering, 2019)
The purpose of this research is to know how much influence of bokashi fertilizer with various types of livestock manure on the production of fresh material, dried material, and organic matter of setaria grass. The material used was spetalata setaria grass. The research method is experimental method with Completely Randomized Design consisting of 4 treatments and 4 replications. The treatments studied were as follows: Treatment A: Setaria grass planted without Bokashi fertilizer, Treatment B: Setaria grass planted with the addition of bokashi pig feces (300gr / polybag), Treatment C: Setaria  grass planted with the addition of bokashi fertilizer from chicken feces (300gr / polybag), Treatment D: Setariara grass planted with the addition of bokashi fertilizer from goat's feces (300gr / polybag). The result of statistical analysis showed that the treatment had no significant effect (P> 0,05) on the production of fresh material, dry matterial and organic matterial of Setaria sphacelata grass.